High-toughness square-bottom bag and preparation method thereof
By adopting a three-layer polymer combination in the square bottom bag, the synergistic effect of polylactic acid, ethylene-vinyl alcohol copolymer, ethylene-acrylic acid copolymer and modified silica is solved, the problem of insufficient toughness of the square bottom bag is solved. , significantly improves its strength and toughness, and is suitable for a variety of packaging fields.
Patent Information
- Application Number
- CN202411740616.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The insufficient toughness and low strength of existing square bottom bags limit their further application in the fields of food, medical, industrial and agricultural packaging.
High toughness square bottom bag design with three-layer structure, in which the inner layer, intermediate layer and outer layer are modified by polyethylene, ethylene-propylene copolymer, polylactic acid, ethylene-vinyl alcohol copolymer, ethylene-acrylic acid copolymer and modified respectively The composition of silica, which improves interlayer binding force and toughness through synergistic effects, specifically includes the definition of the melt index of polylactic acid, the molar content control of ethylene-vinyl alcohol copolymer and ethylene-acrylic acid copolymer, and the modification of silica by PBAT sex.
It significantly improves the toughness and strength of the square bottom bag, improves its packaging performance in different application fields, and meets the needs of high toughness and high strength.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic bags, and in particular to a high-toughness square bottom bag and a preparation method thereof. Background Art
[0002] Plastic bags are made of plastic as the main raw material through processes such as film blowing. They are widely used in various fields because of their advantages of being cheap, large in capacity, and easy to store. Square bottom bags are one type of plastic bags. The bottom of this plastic bag is designed to be square and can be customized according to the size of the packaged product. Square bottom bags are widely used in the packaging of food, medical, industrial, agricultural, and daily necessities, and have good sealing and barrier properties. However, the existing square bottom bags still have the problems of insufficient toughness and low strength, which limits the further application of square bottom bags. Therefore, it is necessary to obtain a square bottom bag with high toughness and high strength. Summary of the invention
[0003] The present invention provides a high-toughness square bottom bag and a preparation method thereof, which solves the problems of poor toughness and low strength of the square bottom bag in the related art.
[0004] The technical solution of the present invention is as follows: The present invention provides a high-toughness square bottom bag, which includes an inner layer, a middle layer, and an outer layer from the inside to the outside; The inner layer comprises the following components in parts by weight: 100 parts of polyethylene, 20-30 parts of ethylene-propylene copolymer, 10-15 parts of polylactic acid, and 1-2 parts of antioxidant; The intermediate layer comprises the following components in parts by weight: 100 parts of ethylene-propylene copolymer, 25-35 parts of ethylene-vinyl alcohol copolymer, and 10-14 parts of silicon dioxide; The outer layer comprises the following components in parts by weight: 100 parts of polyethylene, 6-8 parts of ethylene-acrylic acid copolymer, and 1-2 parts of antioxidant.
[0005] As a further technical solution, the melt index of the polylactic acid at 210°C / 2.16kg is 7-23g / 10min.
[0006] In the present invention, the melt index of polylactic acid at 210°C / 2.16kg is limited to 7-23g / 10min and then coordinated with ethylene-vinyl alcohol copolymer and ethylene-acrylic acid copolymer in different layers to further improve the toughness and strength of the square bottom bag.
[0007] As a further technical solution, the thickness of the inner layer is 0.1-0.15 mm; the thickness of the middle layer is 0.2-0.3 mm; and the thickness of the outer layer is 0.05-0.2 mm.
[0008] As a further technical solution, the molar content of ethylene in the ethylene-vinyl alcohol copolymer is 27% to 38%.
[0009] As a further technical solution, the molar content of acrylic acid in the ethylene-acrylic acid copolymer is 7% to 10%.
[0010] In the present invention, the molar content of acrylic acid in the ethylene-acrylic acid copolymer is limited to 7% to 10%, and then coordinated with the ethylene-vinyl alcohol copolymer and polyacrylic acid located in different layers, so as to further improve the toughness and strength of the square bottom bag.
[0011] As a further technical solution, the silicon dioxide is PBAT modified silicon dioxide.
[0012] In the present invention, PBAT is used to modify silicon dioxide, thereby improving the compatibility of silicon dioxide in the polymer matrix and improving the bonding force between layers, thereby further improving the toughness and strength of the square bottom bag.
[0013] As a further technical solution, the preparation method of PBAT-modified silica comprises the following steps: dissolving PBAT, mixing the mixture with silica, and removing the solvent to obtain PBAT-modified silica.
[0014] As a further technical solution, the mass ratio of PBAT to silicon dioxide is 1:10~14.
[0015] As a further technical solution, the model of the PBAT is BFX3091 and / or C1200.
[0016] As a further technical solution, when the models of the PBAT are BFX3091 and C1200, the mass ratio of PBAT-BFX3091 and PBAT-C1200 is 2:3~3:2.
[0017] In the present invention, the models of PBAT are BFX3091 and C1200, and when the mass ratio of PBAT-BFX3091 to PBAT-C1200 is 2:3 to 3:2, after the silicon dioxide is modified, the toughness and strength of the square bottom bag are further improved.
[0018] The present invention also provides a method for preparing the high-toughness square bottom bag, comprising the following steps: The components of the inner layer, the middle layer and the outer layer are mixed respectively, and then three-layer co-extrusion blown film is formed to obtain a high-toughness square bottom bag.
[0019] The working principle and beneficial effects of the present invention are: In the present invention, the polylactic acid, ethylene-vinyl alcohol copolymer and ethylene-acrylic acid copolymer located in different layers are used to achieve synergy between the inner layer, the middle layer and the outer layer, thereby improving the bonding and toughness between the three layers, and ultimately significantly improving the toughness and strength of the square bottom bag. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] In the following examples and comparative examples, the model of polyethylene is 2420H; the model of ethylene-propylene copolymer is Formosa Plastics Yongjia 3080.
[0022] Example 1 The high-toughness square bottom bag includes an inner layer, a middle layer, and an outer layer from the inside to the outside; the thickness of the inner layer is 0.1mm; the thickness of the middle layer is 0.2mm; the thickness of the outer layer is 0.2mm; The inner layer comprises the following components in parts by weight: 100 parts of polyethylene, 20 parts of ethylene-propylene copolymer, 10 parts of polylactic acid, and 1 part of antioxidant 1076; The middle layer comprises the following components in parts by weight: 100 parts of ethylene-propylene copolymer, 25 parts of ethylene-vinyl alcohol copolymer, and 10 parts of silicon dioxide; The outer layer comprises the following components in parts by weight: 100 parts of polyethylene, 6 parts of ethylene-acrylic acid copolymer, and 10762 parts of antioxidant; Among them, the melt index of polylactic acid at 210℃ / 2.16kg is 6g / 10min (model LX175); the molar content of ethylene in ethylene-vinyl alcohol copolymer is 27% (product number 55207345, from Shanghai Zhenzhun Biotechnology Co., Ltd.); the molar content of acrylic acid in ethylene-acrylic acid copolymer is 6.5% (model 3003); The preparation method of the high-toughness square bottom bag comprises the following steps: The components of the inner layer, the middle layer and the outer layer are mixed separately and then subjected to three-layer co-extrusion blown film forming to obtain a high-toughness square bottom bag.
[0023] Example 2 High-toughness square bottom bag, from inside to outside, includes inner layer, middle layer and outer layer; the thickness of the inner layer is 0.15mm; the thickness of the middle layer is 0.3mm; the thickness of the outer layer is 0.05mm; The inner layer comprises the following components in parts by weight: 100 parts of polyethylene, 30 parts of ethylene-propylene copolymer, 15 parts of polylactic acid, and 2 parts of antioxidant 1076; The middle layer comprises the following components in parts by weight: 100 parts of ethylene-propylene copolymer, 35 parts of ethylene-vinyl alcohol copolymer, and 14 parts of silicon dioxide; The outer layer comprises the following components in parts by weight: 100 parts of polyethylene, 8 parts of ethylene-acrylic acid copolymer, and 10761 parts of antioxidant; Among them, the melt index of polylactic acid at 210℃ / 2.16kg is 6g / 10min (model LX175); the molar content of ethylene in ethylene-vinyl alcohol copolymer is 38% (product number 55207347, from Shanghai Zhenzhun Biotechnology Co., Ltd.); the molar content of acrylic acid in ethylene-acrylic acid copolymer is 6.5% (model 3003); The preparation method of the high-toughness square bottom bag comprises the following steps: The components of the inner layer, the middle layer and the outer layer are mixed separately and then subjected to three-layer co-extrusion blown film forming to obtain a high-toughness square bottom bag.
[0024] Example 3 The high-toughness square bottom bag includes an inner layer, a middle layer, and an outer layer from the inside to the outside; the thickness of the inner layer is 0.1mm; the thickness of the middle layer is 0.2mm; the thickness of the outer layer is 0.2mm; The inner layer comprises the following components in parts by weight: 100 parts of polyethylene, 25 parts of ethylene-propylene copolymer, 12 parts of polylactic acid, and 2 parts of antioxidant 1076; The middle layer comprises the following components in parts by weight: 100 parts of ethylene-propylene copolymer, 28 parts of ethylene-vinyl alcohol copolymer, and 12 parts of silicon dioxide; The outer layer comprises the following components in parts by weight: 100 parts of polyethylene, 8 parts of ethylene-acrylic acid copolymer, and 10761 parts of antioxidant; Among them, the melt index of polylactic acid at 210℃ / 2.16kg is 6g / 10min (model LX175); the molar content of ethylene in ethylene-vinyl alcohol copolymer is 32% (product number 55207346, from Shanghai Zhenzhun Biotechnology Co., Ltd.); the molar content of acrylic acid in ethylene-acrylic acid copolymer is 6.5% (model 3003); The preparation method of the high-toughness square bottom bag comprises the following steps: The components of the inner layer, the middle layer and the outer layer are mixed separately and then subjected to three-layer co-extrusion blown film forming to obtain a high-toughness square bottom bag.
[0025] Example 4 The only difference between this embodiment and embodiment 3 is that the melt index of the polylactic acid at 210° C. / 2.16 kg is 70 g / 10 min (model L105).
[0026] Example 5 The only difference between this embodiment and embodiment 3 is that the melt index of the polylactic acid at 210° C. / 2.16 kg is 7 g / 10 min (model LX575).
[0027] Example 6 The only difference between this embodiment and embodiment 3 is that the melt index of the polylactic acid at 210° C. / 2.16 kg is 23 g / 10 min (model LX530).
[0028] Example 7 The only difference between this example and Example 6 is that the molar content of acrylic acid in the ethylene-acrylic acid copolymer is 25% (Type 5980).
[0029] Example 8 The only difference between this example and Example 6 is that the molar content of acrylic acid in the ethylene-acrylic acid copolymer is 7% (Type 5050).
[0030] Example 9 The only difference between this example and Example 6 is that the molar content of acrylic acid in the ethylene-acrylic acid copolymer is 10% (Type 373).
[0031] Example 10 The only difference between this embodiment and embodiment 9 is that the silicon dioxide is PBAT modified silicon dioxide.
[0032] The preparation method of PBAT modified silica comprises the following steps: dissolving 1 g of PBAT in 40 g of chloroform, adding 12 g of silica to mix, removing chloroform, and obtaining PBAT modified silica; wherein the model of PBAT is BFX3091.
[0033] Embodiment 11 The only difference between this embodiment and embodiment 10 is that the model of PBAT is C1200.
[0034] Example 12 The only difference between this embodiment and embodiment 10 is that PBAT is a mixture of PBAT-BFX3091 and PBAT-C1200 in a mass ratio of 1:4.
[0035] Embodiment 13 The only difference between this embodiment and embodiment 10 is that PBAT is a mixture of PBAT-BFX3091 and PBAT-C1200 in a mass ratio of 4:1.
[0036] Embodiment 14 The only difference between this embodiment and embodiment 10 is that PBAT is a mixture of PBAT-BFX3091 and PBAT-C1200 in a mass ratio of 2:3.
[0037] Embodiment 15 The only difference between this embodiment and embodiment 10 is that PBAT is a mixture of PBAT-BFX3091 and PBAT-C1200 in a mass ratio of 3:2.
[0038] Comparative Example 1 The only difference between this comparative example and Example 3 is that polylactic acid is not added to the components of the inner layer.
[0039] Comparative Example 2 The only difference between this comparative example and Example 3 is that no ethylene-vinyl alcohol copolymer is added to the composition of the intermediate layer.
[0040] Comparative Example 3 The only difference between this comparative example and Example 3 is that no ethylene-acrylic acid copolymer is added to the composition of the outer layer.
[0041] According to the standard GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets", the tensile strength and elongation at break of the square bottom bags prepared in Examples 1 to 15 and Comparative Examples 1 to 3 were tested respectively. The test results are shown in Table 1 below: Table 1 Performance test results
[0042] Compared with comparative examples 1 to 3, the tensile strength and elongation at break of the square bottom bags prepared in embodiments 1 to 15 are higher, indicating that the polylactic acid, ethylene-vinyl alcohol copolymer and ethylene-acrylic acid copolymer located in different layers enable the inner layer, the middle layer and the outer layer to cooperate with each other, thereby significantly improving the toughness and strength of the square bottom bag.
[0043] Compared with Examples 3 to 4, the square bottom bags prepared in Examples 5 to 6 have higher tensile strength and elongation at break, indicating that the toughness and strength of the square bottom bags are further improved by limiting the melt index of polylactic acid at 210°C / 2.16kg to 7 to 23g / 10min and then coordinating with ethylene-vinyl alcohol copolymer and ethylene-acrylic acid copolymer in different layers.
[0044] Compared with Examples 6 and 7, the tensile strength and elongation at break of the square bottom bags prepared in Examples 8 and 9 are higher, indicating that the toughness and strength of the square bottom bags are further improved by limiting the molar content of acrylic acid in the ethylene-acrylic acid copolymer to 7% to 10% and then coordinating with the ethylene-vinyl alcohol copolymer and polyacrylic acid in different layers.
[0045] Compared with Example 9, the tensile strength and elongation at break of the square bottom bags prepared in Examples 10 to 15 are higher, indicating that the use of PBAT to modify silica improves the compatibility of silica in the polymer matrix and the bonding force between the layers, further improving the toughness and strength of the square bottom bag.
[0046] Compared with Examples 10 to 13, the tensile strength and elongation at break of the square bottom bags prepared in Examples 14 to 15 are higher, indicating that when the PBAT models are BFX3091 and C1200, and the mass ratio of PBAT-BFX3091 to PBAT-C1200 is 2:3 to 3:2, the modification of silica further improves the toughness and strength of the square bottom bag.
[0047] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-toughness square bottom bag, characterized in that: From the inside to the outside, it includes the inner layer, the middle layer, and the outer layer; The inner layer comprises the following components in parts by weight: 100 parts of polyethylene, 20-30 parts of ethylene-propylene copolymer, 10-15 parts of polylactic acid, and 1-2 parts of antioxidant; The intermediate layer comprises the following components in parts by weight: 100 parts of ethylene-propylene copolymer, 25-35 parts of ethylene-vinyl alcohol copolymer, and 10-14 parts of silicon dioxide; The outer layer comprises the following components in parts by weight: 100 parts of polyethylene, 6-8 parts of ethylene-acrylic acid copolymer, and 1-2 parts of antioxidant.
2. A high toughness block bottom bag according to claim 1, characterized in that: The melt index of the polylactic acid at 210° C. / 2.16 kg is 7-23 g / 10 min.
3. A high toughness block bottom bag according to claim 1, characterized in that: The molar content of ethylene in the ethylene-vinyl alcohol copolymer is 27% to 38%.
4. A high-toughness block bottom bag according to claim 1, characterized in that: The molar content of acrylic acid in the ethylene-acrylic acid copolymer is 7% to 10%.
5. The high-toughness square bottom bag according to claim 1, characterized in that: The silicon dioxide is PBAT modified silicon dioxide.
6. A high toughness block bottom bag according to claim 5, characterized in that: The preparation method of the PBAT-modified silica comprises the following steps: dissolving PBAT, mixing the mixture with silica, and removing the solvent to obtain the PBAT-modified silica.
7. A high-toughness block bottom bag according to claim 6, characterized in that: The mass ratio of the PBAT to silicon dioxide is 1:10-14.
8. The high-toughness square bottom bag according to claim 6, characterized in that: The model of the PBAT is BFX3091 and / or C1200.
9. A high-toughness block bottom bag according to claim 8, characterized in that: When the models of the PBAT are BFX3091 and C1200, the mass ratio of PBAT-BFX3091 and PBAT-C1200 is 2:3~3:
2.
10. The method for preparing a high-toughness square bottom bag according to any one of claims 1 to 9, characterized in that: The following steps are involved: The components of the inner layer, the middle layer and the outer layer are mixed respectively, and then three-layer co-extrusion blown film is formed to obtain a high-toughness square bottom bag.
Citation Information
Patent Citations
High-barrier bio-based composite membrane and preparation method thereof
CN103950257A
Container bag for buffer solution
CN114229246A
Manufacturing method of multi-layer composite membrane, multi-layer composite membrane and application of multi-layer composite membrane
CN115697699A